PREVENTION OF INSECURE ACCORDING TO THE QURAN: A STUDY OF STUDENTS AT THE DARUL HIKMAH MODERN ISLAMIC BOARDING SCHOOL - Syaripa Hanum Ritonga; Syahrin Harahap (RADJA PUBLIKA, 2026)
This study aims to examine the phenomenon of insecurity among students (santri) at Darul Hikmah Islamic Boarding School and to propose Qur‟anic-based solutions. A qualitative field research approach was employed, using observation, in-depth interviews, and documentation involving 30 students, 2 teachers, and 6 parents. Data were analyzed through data reduction, data display, and conclusion drawing. The findings indicate that insecurity among students is influenced by psychological vulnerability, social comparison, negative verbal experiences, and limited understanding of Islamic self-worth. Observations of religious activities such as halaqah and murāja„ah reveal increased self-awareness and inner calm, although some students continue to experience feelings of inferiority. Psychological impacts include reduced self-confidence and diminished learning engagement. The proposed Qur‟anic solutions emphasize strengthening awareness of human dignity, cultivating inner tranquility through worship, and fostering social ethics that prohibit humiliation and mockery. This study concludes that the Al-Qur’an functions not only as a moral guide but also as a relevant psychological resource for addressing insecurity within contemporary Islamic educational settings.